Efecto fotoprotector solar in vitro del aceite esencial de Ocimum basilicum L. (Albahaca) y Tropaeolum majus L. (Mastuerzo) - Deza Peña, Marck Anthony (2019)
The main objective of this research work was to determine the in vitro sun protection factor of the essential oil of Ocimum basilicum L. and Tropaeolum majus L. which was extracted by the method of water vapor dragging, the process was converted with the Collection of samples of Ocimum basilicum L. in the district of Simbal and Tropaeolum majus L. in the district of Otuzco, then identified in the Herbarium Truxillense (HUT) of the National University of Trujillo with the number for Ocimum basilicum L. 60326 and Tropaeolum majus L. 60327. After obtaining the plant material, the washing and drying proceeded. The extraction of the essential oil of Ocimum basilicum L. (albahaca) was obtained obtaining a yield of 0,3% w/w, which presented the following organoleptic characteristics: oily liquid texture, light yellow color, pleasant smell. The physicochemical characteristics of the essential oil were: density 0,8754 g/mL, pH 4,1; refractive index 1,502 and acid number 0,0012 mg NaOH/g. Likewise, this essential oil was soluble in 96° GL ethanol, moderately soluble in 70° GL ethanol, and insoluble in 50° GL alcohol and water. The in vitro sun protection factor of 0,1% Ocimum basilicum L. essential oil was 6,2922. By applying the steam entrainment distillation method in Tropaeolum majus L. (mastuerzo), it is not possible to obtain essential oil